Simple Synthesis of TiO2/MnOx Composite with Enhanced Performances as Anode Materials for Li-Ion Battery. (1st September 2016) - Wu, Di; Yang, Rong; Sun, Qingxia; Shen, Li; Ji, Wenxu; Shen, Rui; Jiang, Meng; Ding, Weiping; Peng, Luming
Graphical abstract: A TiO2 /MnOx composite was prepared in mild conditions as a new anode material with enhanced electrochemical properties for lithium ion battery Abstract: Hydrolysis of organic titanate was used to modify γ-MnO2 to produce a TiO2 /MnOx composite as a new anode material with enhanced electrochemical properties for lithium ion battery. The composition, structure, valence state as well as the lithium storage mechanism of the composite have been carefully studied with inductively coupled plasma (ICP) elemental analysis, X-ray diffraction(XRD), electron microscopy, X-ray photoelectron spectroscopy (XPS) and solid-state nuclear magnetic resonance (NMR) spectroscopy. The electrochemical measurement shows that the specific capacity of the composite stays above 972 mAh/g for 100 cycles at a current rate of 100 mA/g, which is much better than γ-MnO2 . The significant improvement can be ascribed to the involvement of both insertion and conversion lithium storage mechanisms owing to the incorporation of a small amount of TiO2 (∼5%) to MnO2, as well as the presence of Mn2 O3 in the composite. This new strategy is expected to be extended to improve the electrochemical properties of other metal oxides for lithium ion battery applications.